Fabrication of a colorimetric sensor using acetic acid-capped drug-mediated copper oxide nanoparticles for nitrite biosensing in processed food - Nishan, Umar; Rehman, Sajida; Ullah, Riaz; Bari, Ahmed; Afridi, Saifullah; Shah, Mohibullah; Iqbal, Jibran; Asad, Muhammad; Badshah, Amir; Khan, Naeem; Hwang, In Min; Khan, Hameed Ullah; et al. (Frontiers in Materials, 2023)
Nitrite (NO2−) and nitrate (NO3−) are frequently used in cured meat products as preservatives, as they give a better taste and work well in color fixation. As a key possible carcinogen, excessive dietary consumption of NO2− in cured meat products would be bad for health. Herein, copper oxide nanoparticles (CuO NPs) were synthesized using the drug Augmentin as a reducing and capping agent. The desired synthesis of CuO NPs was confirmed by various characterization techniques, including UV–visible spectroscopy, Fourier transform infrared spectroscopy, energy-dispersive X-ray spectroscopy, thermal gravimetric analysis, X-ray diffraction, and scanning electron microscopy. The new approach of drug-mediated acetic acid-capped CuO NPs was developed for simple colorimetric detection of nitrite ions in a mimic solution of processed food. The color of the detection system changes from brown to yellow with the increase in the concentration of NO2− and has been observed with the naked eye. The selectivity of the NO2− detection system by the UV–visible spectrum and the naked eye is compared to other ions, such as Br−, I−, Cl−1, PO4−3, CO32−, and SO42−. The platform was successfully employed for the determination of nitrite in real samples. Moreover, this probe can be used for the sensitive detection of NO2− with a linear range of 1 × 10−8 to 2.40 × 10−6 M, a detection limit of 2.69 × 10−7 M, a limit of quantification 8.9 × 10−7 M, and a regression coefficient (R2) of 0.997. Our results suggest that this sensor can be used for on-site analysis and quantification as well as in the fields of disease diagnosis, environmental monitoring, and food safety.